(untitled) (World Bulletin of Public Health, 2022)
The article examines the epidemiological situation of HIV infection in Samarkand region, outlines the regulatory documents on prevention of HIV infection and the necessary preventive measures for pregnant women. In our country, special attention is paid to measures to counter the spread of HIV infection. In the context of the ongoing epidemic, it is difficult to overestimate the importance of preventive measures, particularly the involvement of the population in HIV testing, including women, who are one of the key groups determining the epidemic spread of HIV infection in our country.